Guiding Ideas from Mind to Market : Learning from infoDev's Mobile Microwork Innovation Competition - World Bank (Washington, DC, 2014)
The Information for Development Program's (InfoDev) "From Mind to Market" approach was designed to bridge early-stage innovation support gaps and guide promising ideas on toward minimum viable products, ultimately turning them into sustainable businesses. The approach aims to source ideas from a large talent pool and spur the best innovators to turn their innovations into sustainable, growth-oriented start-ups. The primary goal is start-up creation. Secondary goals include the generation of pools of ideas and prototypes, the creation of basic topical knowledge for a large group of innovators, and broader awareness-raising around a new topic, as well as partnership and capacity-building for implementation partners. This report summarizes the approach, which is based on four steps: 1) the identification of a novel topic with market potential and high potential for international development; 2) the implementation of a broad based collaborative, open innovation competition; 3) the implementation of an activity that forges minimum viable products through face-to-face support at sites across the globe; and 4) the follow-up with a program of incubation and acceleration for the best and most committed innovators.